2017
DOI: 10.4049/jimmunol.1700023
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Form of Carlr lncRNA Facilitates Inflammatory Gene Expression upon NF-κB Activation

Abstract: Long non-coding RNAs (lncRNAs) have emerged as critical regulators of inflammation. To further understand the interaction between inflammatory signaling pathways and lncRNAs, we characterized the function of the lncRNA, Carlr, a lncRNA expressed in both mouse and human cells of diverse tissues. Carlr expression is increased following NF-κB signaling in macrophages, with concomitant translocation to, and enrichment of, the transcript in the cytoplasm. Knockdown of Carlr results in impaired expression of NF-κB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…At the same time, NF‐κB signalling caused changes in other lncRNAs that have been shown to be important for both cytokines production and subsequent resolution of inflammation. Compared with control patients, three of the putative Carlr‐regulated targets, TNFAIP3, IL1B and PTGS2, showed statistically significant higher expression in coeliac patients …”
Section: Inflammatory Diseases Induced By Dysregulation Of Lncrnas Anmentioning
confidence: 88%
“…At the same time, NF‐κB signalling caused changes in other lncRNAs that have been shown to be important for both cytokines production and subsequent resolution of inflammation. Compared with control patients, three of the putative Carlr‐regulated targets, TNFAIP3, IL1B and PTGS2, showed statistically significant higher expression in coeliac patients …”
Section: Inflammatory Diseases Induced By Dysregulation Of Lncrnas Anmentioning
confidence: 88%
“…lncRNAs that have been reported to be associated with CC include metastasis associated lung adenocarcinoma transcript (MALAT-1) ( 26 ), MEG3( 27 ) and small nucleolar RNA host gene 1( 25 ), among others. Of note, previous studies have demonstrated that NKILA expression is decreased in breast cancer ( 28 ), tongue squamous cell carcinoma (TSCC) ( 11 ) and non-small cell lung cancer (NSCLC) ( 29 ), where it was suggested to be involved in tumor progression by serving as a tumor suppressor gene. Consistent with these studies, the present study also observed decreased expression levels of NKILA in CC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Li et al ( 47 ) found that in human proximal tubular HK-2 cells co-cultured with monocytes, the activation of NF-κB increased intercellular adhesion molecule1expression levels to induce EMT and Wang et al ( 48 ) demonstrated that the activation of NF-κB induced EMT phenotypic changes in human CC stem cells. Recently, a novel mechanism of action for lncRNAs has been reported, in which NKILA was observed to directly inhibit the NK-κB-mediated apoptosis and invasion of breast cancer cells through blocking the phosphorylation site of IκB that directly interacts with NF-κB ( 28 ). Huang et al ( 11 ) reported that NKILA inhibited the migration and invasion of TSCC cells in vitro , as well as inhibiting lung metastasis in NOD/SCID mice with TSCC tumors in vivo ; the NF-κB pathway was found to mediate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for chromatin remodeling via lncRNAs was shown in a study where lincRNA-Tnfaip3 was found in the LPS-stimulated macrophages to regulate high-mobility group box 1 (Hmgb1)-associated histone modification and the subsequent NF-κB-mediated transactivation of pro-inflammatory genes [126]. Other studies in murine bone marrow-derived macrophages demonstrated that the expression of the lncRNA cardiac and apoptosis-related lncRNA (Carlr) is not only directly increased by NF-κB activation but, more importantly, its knockdown results in significantly reduced expression levels of several NF-κB-regulated genes, such as the nuclear factor of the kappa light polypeptide gene enhancer in B cells 2, p49/p100 (Nfkb2), prostaglandin-endoperoxide synthase 2 (Ptgs2), interleukin 1 alpha (Il1a), and interleukin 1 beta (Il1b) [127].…”
Section: Lncrna Involved In the Macrophage Tlr Activation And Signalingmentioning
confidence: 99%